2006
DOI: 10.1002/eat.20349
|View full text |Cite
|
Sign up to set email alerts
|

A history of human‐like dieting alters serotonergic control of feeding and neurochemical balance in a rat model of binge‐eating

Abstract: Despite lack of hunger, a history of human-like dieting alters serotonin function in ways suggesting consequences not only to feeding but also control of reward and mood that are dependent on dopamine/serotonin interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…This increase in sucrose-licking activity in the LS-lesioned rats was independent from thirsting or fasting and was not eliminated by sucrose preloading (9). In addition to the plausible implication of the LS, the alterations in the activity of the dopamine, serotonin, and opioid systems may be involved in the mechanisms of regulation of feeding behavior in rats submitted to intermittent eating of palatable food (5,7,12,15,17,18,68,83).…”
Section: Discussionmentioning
confidence: 88%
“…This increase in sucrose-licking activity in the LS-lesioned rats was independent from thirsting or fasting and was not eliminated by sucrose preloading (9). In addition to the plausible implication of the LS, the alterations in the activity of the dopamine, serotonin, and opioid systems may be involved in the mechanisms of regulation of feeding behavior in rats submitted to intermittent eating of palatable food (5,7,12,15,17,18,68,83).…”
Section: Discussionmentioning
confidence: 88%
“…Despite the robustness of the HD+Stress model to alterations in experimental manipulations by us and others [33, 43, 53, 6062, 8992], we have not always been able to obtain binge-eating in the rats. Sometimes others, also, could not obtain the effect with foot shock or if they did, the binge-eating was attenuated [91, 92].…”
Section: The History Of Dieting + Stress (Hd+stress) Modelmentioning
confidence: 80%
“…Indeed, subsequent work from the Boggiano lab found that rats with a HD developed neurochemical and behavioral changes consistent with anhedonia despite normal energy balance. This was true regardless of experience with or without stress [53] and whether rats had intermittent, daily, or no exposure to palatable food during the HD [53, 54]. Translating to humans, “forbidden foods” (typically palatable foods) are often consumed during a binge [55, 56].…”
Section: The History Of Dieting + Stress (Hd+stress) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound decreases the frequency of binge eating episodes and its severity and has been used before in animal models to inhibit binge eating-like behavior (36, 4447). Therefore, we decided to evaluate if the administration of fluoxetine was able to inhibit the SBLB in our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%